Macromorphological and micromorphological seed features of selected taxa of Caesalpiniaceae using light and scanning electron microscopy. Issue 7 (22nd March 2019) - Ullah, Farhat; Ahmad, Mushtaq; Zafar, Muhammad; Jabeen, Asma; Sultana, Shazia; Ghani, Abdul; Luqman, Muhammad; Nazish, Moona; Alam, Fakhre
Abstract: Seed micromorphological and macromorphological characteristics of 12 taxa of Caesalpiniaceae from Pakistan have been studied, using light and scanning electron microscopy, to investigate the importance of seed coat features as a taxonomic tool. Great variations have been observed in color, shape, dimension, and seed surface pattern among the different genera of the family. A taxonomic key was prepared for the studied taxa. Six types of seed shapes were observed; circular, elliptical, irregular, oblong, oval, and ovoid. All examined seeds were hard except fragile seeds of Haematoxylom campechianum . Eight types of surface ornamentation have been noticed that include levigate, lugose, papillate, reticulate, reticulate irregular, reticulate regular, rhombus, and rogues. Majority of the taxa has been observed with thick ornamentation wall but thin ornamentation wall has also been recorded in few species. Fracture line of the various patterns was present in all taxa except genus Bauhinia . Three types of texture crudeness; coarse, medium, and fine have been recorded. Both micromorphological and macromorphological characters of seed are very fruitful in identification and classification of Caesalpiniaceae. Abstract :